Pelatihan Pengembangan Media Pembelajaran Interaktif untuk Guru PJOK di KKGO Manggala Kota Makassar - Juhanis Juhanis; Fatoni Fatoni; Abriadi Abriadi; Iskandar Iskandar; Nur Indah Atifah Anwar (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
This community service activity was carried out with the aim of improving the competence of Physical Education, Sports, and Health (PESH) teachers in developing interactive learning media based on digital technology. Many PESH  teachers at KKGO Manggala, Makassar City, still use conventional methods and face limitations in the use of digital media, resulting in less than optimal learning in attracting student interest and motivation. This training is designed to provide theoretical knowledge, practical practice, and hands-on experience in designing interactive learning media relevant to PESH material. The implementation method of the activity includes preparation, implementation, and evaluation stages. In the preparation stage, modules are prepared and coordination with KKGO administrators is carried out. The implementation stage includes material presentations, practical workshops on creating media using applications such as Canva and interactive PowerPoint, and intensive mentoring in product development. Furthermore, evaluation is carried out through pre-tests, post-tests, observations, and reflections with participants. The results of the activity show a significant increase in teacher knowledge and skills in developing interactive learning media. In addition, this activity also encourages creativity, collaboration, and teacher motivation to innovate in PESH learning. Thus, this training provides a real contribution to improving the quality of PESH learning and is worthy of being developed sustainably and scientifically in other regions.